1968 and beyond. The urban struggle on trial? - Doucet, Isabelle (Routledge, 2021)
This chapter relates, in translation, and accompanied by an introduction, a conversation with Maurice Culot, one of the protagonists of the Reconstruction of the European City movement that sprouted from the Right to the City activism of the 1970s. I have used this occasion to prompt questions about researching urban ethics. The conversation offers a discussion on the origins of the Reconstruction of the European City model at a time when we are still living through the legacies of the movement. It prompts questions regarding the discussion of urban ethics through theories, ideologies and designs for the urban condition and the (long-term) effects and transformations. I take this conversation, despite its informal and probing nature, as an invitation to revisit the political ambiguities and aesthetic translations at the origins of the movement and address the (desired and undesired) effects over nearly five decades. Despite its tentative nature, the interview offers a modest attempt to begin revisiting more thoroughly some of the opportunities, struggles and challenges of the Reconstruction of the City approach to urban ethics.
Keywords: Europäische Stadt; Kritische Rekonstruktion; Planungsleitbild; Wertvorstellung; Stadtbild; Ethik; Planungsansatz; Recht auf Stadt